Financial Literacy and Financial Technology: Factors Influencing Increased Financial Inclusion in Communities in Sumedang Regency - Meltarini (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study discusses the factors that influence the improvement of financial inclusion in the community in Sumedang Regency. The survey results show that financial inclusion in Sumedang Regency is still low, with higher levels of financial access in urban areas than rural areas. Factors supporting financial inclusion, such as accessibility, awareness and education, affordability, and technology and innovation, play an important role in improving financial inclusion. Financial literacy and financial technology (fintech) adoption play a crucial role in improving financial inclusion in Sumedang Regency. This research suggests that improving accessibility, awareness and education, affordability, and technology and innovation can help improve financial inclusion in Sumedang Regency